XANES and DRIFTS study of sulfated Sb/V/Ce/TiO2 catalysts for NH3-SCR - Kumar, Pullur Anil; Jeong, Young Eun; Gautam, Sanjeev; Ha, Heon Phil; Lee, Kyung Ju; Chae, Keun Hwa (ELSEVIER SCIENCE SA, 2015)
A study of structural and mechanistic investigation of the Sb/V/Ce/Ti catalysts sulfated at different temperatures was carried out by X-ray absorption near edge spectroscopy (XANES) and diffused reflectance infrared Fourier transformed spectroscopy (DRIFTS). The high temperature sulfated catalyst, especially Sb/V/Ce/Ti-S500 (sulfated at 500 degrees C temperatures), exhibited superior NO conversion at low temperatures (150-200 degrees C) compared to Sb/V/Ce/Ti-S400 and Sb/V/Ce/Ti-S300 (sulfated at 400 and 300 degrees C) catalysts. The Ce L-3 edge XANES spectra of Sb/V/Ce/Ti-S500 catalyst showed the formation of Ce(III) dominant sulfate species, resulting in the enhancement of Lewis and Bronsted acid strength. The formation of Ce(III) sulfate species on Sb/V/Ce/Ti-S500 catalyst was clearly indicated by Ce M-4,M-5 and S K edge XANES spectra peaks at 881.9 eV attributed to Ce3+ oxidation state and 2481 eV assigned to S6+ oxidation state of sulfate species. Furthermore, the in situ DRIFTS results revealed that the Lewis and Bronsted acid sites of Sb/V/Ce/Ti-S500 catalysts increased significantly, followed by Sb/V/Ce/Ti-S400 and Sb/V/Ce/Ti-S300. At 200 degrees C, the reaction between the pre-adsorbed NH3 species with NO + O-2 on sulfated catalysts exhibited the formation of mono-dentate, bi-dentate, bridging nitrates and NO2 species. Meanwhile, the subsequent formation of NO2 via NO oxidation was promoted on Sb/V/Ce/Ti-S400 and Sb/V/Ce/Ti-S500 catalysts, followed by surface interaction with adsorbed NH3 to produce N-2 and H2O at low temperatures (<220 degrees C). (C) 2015 Elsevier B.V. All rights reserved.
Keywords: LOW-TEMPERATURE SCR; SO2 OXIDATION; NITRIC-OXIDE; X-RAY; MECHANISTIC ASPECTS; NOX REDUCTION; NH3; CERIA; CEO2; AMMONIA